2020
DOI: 10.3390/min10080697
|View full text |Cite
|
Sign up to set email alerts
|

Derivation of Predicted No Effect Concentrations (PNECs) for Heavy Metals in Freshwater Organisms in Korea Using Species Sensitivity Distributions (SSDs)

Abstract: Natural and artificial heavy metal exposure to the environment requires finding thresholds to protect aquatic ecosystems from the toxicity of heavy metals. The threshold is commonly called a predicted no effect concentration (PNEC) and is thought to protect most organisms in an ecosystem from a chemical. PNEC is derived by applying a large assessment factor (AF) to the toxicity value of the most sensitive organism to a chemical or by developing a species sensitivity distribution (SSD), which is a cumulative di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 28 publications
(49 reference statements)
0
3
0
1
Order By: Relevance
“…Studies have shown that the predicted no-effect concentration (PNEC) for caffeine in rivers is 5.2 ppb (Komori et al, 2013). The PNEC marks the critical concentration at which an ecosystem can be adversely affected (Park and Kim, 2020). Another study determined 0.05 ppb to be the PNEC of caffeine on algae, invertebrates, and fishes (Szymczycha et al, 2020).…”
Section: Figurementioning
confidence: 99%
“…Studies have shown that the predicted no-effect concentration (PNEC) for caffeine in rivers is 5.2 ppb (Komori et al, 2013). The PNEC marks the critical concentration at which an ecosystem can be adversely affected (Park and Kim, 2020). Another study determined 0.05 ppb to be the PNEC of caffeine on algae, invertebrates, and fishes (Szymczycha et al, 2020).…”
Section: Figurementioning
confidence: 99%
“…Wang et al constructed SSD curves to evaluate ecological risks of marine organisms (including crustacean, fish and mollusc) induced by five heavy metals (including Cu, Zn, Pb, Hg and As) in China’s coastal waters, and found that there were a certain high ecological risk point in Bohai Sea caused by Cu and Zn 10 . Park and Kim applied the SSD method to obtain the ecological risk threshold values of Cd, Cu, Pb and Zn for aquatic organisms living in Korea 36 . When evaluating the risk of aquatic organisms induced by heavy metal, SSD and ICE take into account the relationship between different species, the uncertainty caused by model selection, data availability and variances, and obtain the prediction and confidence interval through probability statistics, which greatly improves the reliability and credibility of the assessment results 32 .…”
Section: Introductionmentioning
confidence: 99%
“…Cu compounds can cause significant risks to the aquatic environment. They are considered harmful to aquatic ecosystems, and crustaceans are considered the most sensitive organisms [95]. Fish, on the other hand, exhibit a wide range of toxicity values, but their ability to reproduce and grow can be impaired when chronically exposed to Cu [109].…”
mentioning
confidence: 99%